DEWAN KOMISARIS DAN INTELLECTUAL CAPITAL DISCLOSURE PADA PERBANKAN DI INDONESIA - Lia Uzliawati (University of Merdeka Malang, 2015)
The purpose of this study is to examine the relationship between board of commissioner and intellectual capitaldisclosure in Indonesia Banking Industry.The purpose of this study was to examine the relationship betweenthe board of commissioner and intellectual capital disclosure in Indonesia Banking Industry. The intellectualcapital disclosure measurement in this study used the index developed by Sveiby (1997).The data were collectedfrom 31 banks listed in Indonesia Stock Exchange period 2008-2012. The disclosure of intellectualcapital measurement in this study used the index developed by Sveiby (1997). The Data were collected from 31banks listed in Indonesia Stock Exchange period 2008-2012. This study finds that size, independent commissioner,and meeting frequency have positive relationship with intellectual capital disclosure. This study foundthat the size, independent commissioner, and meeting frequency had a positive relationship with intellectualcapital disclosure. The finding of this research can be as a reference and portrait that board of commissioneralready aware the importance of ICD. The finding of this research could be as a reference and portrait thatboard of commissioner was already aware of the importance of ICD.